The Problem of Socialization in the General Sociological Theory of Heinrich Popitz - Emanuel Gros, Alexis (Nómadas. Critical Journal of Social and Juridical Science, 2013)
This paper aims to give an overview of the barely unknown work of the German sociologist Heinrich Popitz (1925-2002) taking as a starting point his account of the problem of socialization (Sozialisation). In order to achieve this aim, I reconstruct the way in which that problem is treated in three of the many sub-theories that coexist within his General Sociological Theory (allgemeine soziologische Theorie), namely: (i) The sub-theory of power, (ii) the sub-theory of ontogenesis of subjectivity and (iii) the sub-theory of social norms.
Keywords: Heinrich Popitz; sociological theory; socialization; social norms; power